Prince of Persia, the sands of time [videorecording (DVD)] - Newell, Mike, 1942-; Arterton, Gemma; Gyllenhaal, Jake, 1980-; Molina, Alfred, 1953-; Kingsley, Ben, 1943- (Walt Disney Studios Home Entertainment : Distributed by Buena Vista Home Entertainment, 2010)
It's a race against time when a rogue prince (Jake Gyllenhaal) reluctantly teams up with a rival princess (Gemma Arterton) to safeguard a magical dagger that gives its possessor the power to reverse time and rule the world.